Gaps between Policy and Implementation - Syahbana, Joesron Alie; Mahnunah, Niâ€™mah (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2014)
Most of the slums are located in coastal areas because the coastal areas are strategic locations which are close to the main livelihoods as fishermen. Agung Ridlo,Â  Sultan Agung University, conducted a study resulted that one of the slums location is Kelurahan Tanjungmas. Same study also resulted that North Semarang has a specific attraction for migrants because its location is the center of trade and industry. The migrants came and looked for places to stay near their factories or beaches. Thus, slum areas were formed gradually. This research is aimed to examine the gaps between the poverty alleviations in managing slum upgrading and their implementation in coastal Semarang City, Kelurahan Tanjungmas. The research method is qualitative method by using qualitative descriptive analysis technique. Data collecting process was conducted by interview to the local government using purposive sampling and the local community using snowball sampling. The study result finds gaps between policy and implementation of houses improvement program were caused by unsuccessful implementation. Gaps also influenced by three external factors namely physical condition, lack of input, and weakness of one stages. Overall, gaps between the policy and implementation of houses improvement program made the program cannot achieve its significant objectives and made the community feel disappointed with the program implementation.